A (in) segurança jurídica das decisões judiciais no Tribunal Superior Eleitoral: análise da cassação de mandatos por abuso de poder econômico - Barboza, Juliana Costa (2019)
The dissertation deals with the study of legal security in Electoral Law, through the High Electoral Court, exercising intense interpretive activity to apply the fragmented legislation of the specialized subject in cases that result in the cassation of elective term of governors. It should be noted that in view of the large number of scattered laws and lack of an organized and current Electoral Code to guide the matter, the Electoral Judiciary expands in its consultative and jurisdictional functions to apply the current legislation to concrete cases. However, it is evident that the normative clarity, specifying in detail how the magistrate should act in certain factual situations, brings stability to the legal system and uniformity in the judgments pronounced by the judges. This situation has been proven in the research through the change occurred in article 224 of the Electoral Code, which included paragraphs 3 and 4 by Law No. 13.165 / 2015, providing for the holding of additional elections in case of a judicial decision that determines the cassation of the elective term. Even with the impasse of the unconstitutionality of the expression "after the final res judicata", later declared by the STF, there was a greater certainty in the positions of the TSE ministers in expressing their votes. On the other hand, it was verified that in the previous judgments on the subject, there were many divergences in the reasoning of the judgments announced in the Superior Electoral Court, pointing out in several moments the existence of legal uncertainties in the jurisprudence collected. In order to prove the existence of legal uncertainty jurisprudential, the reasons for the votes of the seven TSE precedents were analyzed in depth, which determined the cassation of the elective term of governors, as well as the decision of the STF of unconstitutionality declared in ADIN nº 5525. In order to overcome the vulnerability factors of legal certainty pointed out in the research, it is concluded that there is a need to organize and systematize legislation in order to better elucidate the interpretative activity performed by magistrates, in addition to intending to form an Electoral Judiciary composed of judges of career.